2014
DOI: 10.2527/jas.2013-6518
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dry matter intake, dry matter digestibility, and feeding behavior on body weight gain of beef steers1,2,3

Abstract: This study was conducted to determine the relative contribution of feeding behavior, DMI, apparent DM digestibility (DMD), and passage rate on variation in BW gain. One hundred forty-three crossbred steers were used in this study to determine the factors that contribute to variation in BW gain. Steers were 304 ± 1 d of age and had an initial BW of 338 ± 3 kg. Steers had ad libitum access to feed, and fresh feed was offered twice daily at 0800 and 1500 h. Individual feed intake and BW gains were determined for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
(30 reference statements)
0
8
0
2
Order By: Relevance
“…Intake of DM is a function of meal size and meal frequency. Davis et al (2014), studying feeding behavior in beef steers, showed that DMI was positively related to the number of meals consumed and the size of each meal. Cows fed the acidogenic diets had longer but fewer meals, with no difference in meal size or eating rate.…”
Section: Discussionmentioning
confidence: 99%
“…Intake of DM is a function of meal size and meal frequency. Davis et al (2014), studying feeding behavior in beef steers, showed that DMI was positively related to the number of meals consumed and the size of each meal. Cows fed the acidogenic diets had longer but fewer meals, with no difference in meal size or eating rate.…”
Section: Discussionmentioning
confidence: 99%
“…high-RFI animals because the reduced DMI and had similar ADG. The greater preference of low-RFI animals for particles larger than 19 and 8 mm may explain the fact that these animals took longer to consume and ruminate a kilogram of both NDF and DM, which may have led to greater ruminal retention time, potentially explaining the lower DMI (Davis et al, 2014). On the basis of this fact, several studies have shown that low-RFI animals have greater nutrient digestibility Nkrumah et al, 2006;Cruz et al, 2010) than high-RFI animals, which may also explain the greater G:F of low-RFI yearling bulls.…”
Section: Rfi Groupmentioning
confidence: 99%
“…In fact, Davis et al . (2014) demonstrated that DM digestibility was correlated with consumption, digestible DM intake and BW gain in multiple regression models.…”
Section: Discussionmentioning
confidence: 99%